The Modern Reform of Arabic Learning Paradigm and Its’ Contribution toward the Development of Islamic Studies - Heni Verawati; Uswatun Hasanah (Al-Lisan: Jurnal Bahasa, 2021)
Arabic learning is positively associated with the growth of Islamic studies. The better comprehension and mastery of Arabic, the faster and the greater the standard of Islamic studies would be. It can also be considered an effort to avoid any misconceptions or misinterpretations in understanding Islam's primary sources (Quran and Hadits) written in Arabic. Therefore, there is a need for more in-depth and continuous study to develop effective Arabic language learning, especially in a modern context. This paper aims to examine some of the previous discussions and research on reforming Arabic language learning to develop Islamic studies in a modern context. Arabic learners today are different from learners in the past who focus more on routine activities by relying on written sources. In this modern era, learners have complete access and freedom to determine the direction of learning they want and need for themselves. Moreover, the main priority in improving Arabic learning quality is by optimizing modern media and technology. Therefore, Arabic language experts need to partner and synergize with competent human resources to develop modern Arabic education and learning technology to produce a better education system in Arabic Learning and support Islamic Studies' development.